The Investigation of Linguistic Contrains in Writing Faced by Junior High School Students - Mirda Mirda; Bukhari Daud; Yuliana Natsir (Universitas Syiah Kuala, 2017)
This thesis was conducted to investigate the language constraints in writing that experienced by the second grade of junior high school students at Ishafuddin, Banda Aceh. It is also to see the teachers’ efforts in helping the students in solving the problems. The research design of this study is descriptive qualitative. The sample of this study are two teachers at second grade of junior high school Inshafuddin. This study used documentation and interview as instruments. The result of document collection showed that the biggest problems faced by the students was mechanics, followed by vocabulary and the content as the third problem. The last problem was organization. From the interview, it was found that the two teachers help the students with all the aspects of writing as well as additional effort like giving them assignment, bringing the dictionary, asking them to study outside the classroom, and correcting paper wih students.